2012
DOI: 10.1167/iovs.11-8786
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Comparison of Corneal Nerve Regeneration and Keratocyte Reaction between FS-LASIK, OUP-SBK, and Conventional LASIK

Abstract: PURPOSE. We compared the regeneration characteristics of injured corneal subbasal nerve fibers (CSNFs) and keratocyte reaction following LASIK with a femtosecond laser (FS-LASIK), One Use-Plus Sub-Bowman's keratomileusis (OUP-SBK), and M2 90 microkeratome to provide a more suitable treatment strategy. METHODS.A total of 22 eyes that underwent FS-LASIK, 32 eyes that underwent OUP-SBK, and 26 eyes that underwent conventional LASIK were analyzed by confocal microscopy. Morphologic modifications of corneal archite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Patel et al [13] demonstrated that the postoperative subbasal nerve densities observed 12 months after FS-LASIK and conventional LASIK were significantly lower than the preoperative densities. Zhang et al [14] reported that corneal subbasal nerve fibers were detectable about 3 mm from the center of the flap in 62.5% of FS-LASIK-treated eyes at the 3-month visit and 100% of FS-LASIK-treated eyes at the 6-month visit. Consistent with previous studies, our results indicated that corneal subbasal nerve fibers were detectable in 56.6% of FS-LASIK-treated eyes at postoperative month 3 and in 100% of FS-LASIK-treated eyes at postoperative month 6.…”
Section: Discussionmentioning
confidence: 99%
“…Patel et al [13] demonstrated that the postoperative subbasal nerve densities observed 12 months after FS-LASIK and conventional LASIK were significantly lower than the preoperative densities. Zhang et al [14] reported that corneal subbasal nerve fibers were detectable about 3 mm from the center of the flap in 62.5% of FS-LASIK-treated eyes at the 3-month visit and 100% of FS-LASIK-treated eyes at the 6-month visit. Consistent with previous studies, our results indicated that corneal subbasal nerve fibers were detectable in 56.6% of FS-LASIK-treated eyes at postoperative month 3 and in 100% of FS-LASIK-treated eyes at postoperative month 6.…”
Section: Discussionmentioning
confidence: 99%
“…314316 However, flaps created using One Use-Plus Sub-Bowman’s keratomileusis (OUP-SBK) had faster nerve regeneration compared to those created with a femtosecond laser or an M2 90 microkeratome. 315 Several studies have shown the effect of the hinge position on the recovery of corneal nerves and sensitivity. Nerve density diminishment varies in different regions within the LASIK flap, being spared on the side of the hinge, and influencing nerve regrowth and corneal sensitivity recovery.…”
Section: Corneal Nerve Alterations After Corneal Surgerymentioning
confidence: 99%
“…Long‐standing post‐operative corneal nerve damage may explain that some patients have persistent dry eye symptoms after surgery. The regeneration of corneal subbasal nerve fibres starts at one month after LASIK and the recovery begins in the peripheral cornea . Abnormal morphology and architecture of restored corneal nerves were noticed after LASIK .…”
Section: Aetiologymentioning
confidence: 99%